2018
DOI: 10.1080/14760584.2018.1510327
|View full text |Cite
|
Sign up to set email alerts
|

Progress on norovirus vaccine research: public health considerations and future directions

Abstract: Noroviruses are the leading cause of foodborne illness worldwide, account for approximately one-fifth of acute gastroenteritis (AGE) cases globally, and cause a substantial economic burden. Candidate norovirus vaccines are in development, but there is currently no licensed vaccine. Areas covered: Noroviruses cause approximately 684 million cases and 212,000 deaths per year across all age groups, though burden estimates vary by study and region. Challenges to vaccine research include substantial and rapidly evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 102 publications
(114 reference statements)
2
56
0
Order By: Relevance
“…Our survey results indicate that providers support vaccine introduction and do not believe their patients receive too many vaccines. With norovirus vaccine candidates currently in phase I and II clinical trials [5], this support will facilitate new vaccine introduction in future years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey results indicate that providers support vaccine introduction and do not believe their patients receive too many vaccines. With norovirus vaccine candidates currently in phase I and II clinical trials [5], this support will facilitate new vaccine introduction in future years.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of disease is substantial; children <5 years of age have the highest rates of norovirus-associated medical visits [2], while older adults are at greatest risk for norovirus-associated deaths [3,4]. Several candidate vaccines are currently in clinical trials, including an oral tablet vaccine that recently reported phase I results from a bivalent GI.1/GII.4 formulation in adults, as well as a bivalent GI.1/GII.4 consensus sequence virus-like particle intramuscular vaccine candidate that has conducted phase II trials in children, adults, and the elderly [5][6][7]. Despite the large burden of disease, practicing physicians may not be aware of the importance of norovirus as a cause of AGE.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, prophylactic and therapeutic vaccines targeting different viruses, such as rotavirus, norovirus, and enterovirus, have evolved with the maturity of VLP vaccine technology (Table 1). These new vaccines are expected to prevent more human diseases [76,101,102].…”
Section: Research Progress On Vlp-based Vaccines In Developmentmentioning
confidence: 99%
“…In addition to providing insights about fundamental virus biology, hsMNV also offers a platform for the development of a thermostabilised vaccine against noroviruses. Most norovirus vaccine candidates under development are VLPs [32]. VLPs lack a viral genome, which can provide stabilising interactions with the capsid [33].…”
Section: Plos Biologymentioning
confidence: 99%